2018
DOI: 10.1038/s41398-018-0194-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light interaction with GluN1 modulates neurotransmission and schizophrenia-associated behaviors

Abstract: Neurofilament (NFL) proteins have recently been found to play unique roles in synapses. NFL is known to interact with the GluN1 subunit of N-methyl-d-aspartic acid (NMDAR) and be reduced in schizophrenia though functional consequences are unknown. Here we investigated whether the interaction of NFL with GluN1 modulates synaptic transmission and schizophrenia-associated behaviors. The interaction of NFL with GluN1 was assessed by means of molecular, pharmacological, electrophysiological, magnetic resonance spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 78 publications
(83 reference statements)
6
51
0
Order By: Relevance
“…Golgi staining for spine density and morphology Golgi staining was performed using the FD Rapid Golgi Stain kit (FD NeuroTechnologies) as previously described (Yuan et al, 2018). Spines were sampled on 3-4 dendrites on each of 3 cells per area, per animal, in the dorsal hippocampus.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
“…Golgi staining for spine density and morphology Golgi staining was performed using the FD Rapid Golgi Stain kit (FD NeuroTechnologies) as previously described (Yuan et al, 2018). Spines were sampled on 3-4 dendrites on each of 3 cells per area, per animal, in the dorsal hippocampus.…”
Section: Novel Object Recognitionmentioning
confidence: 99%
“…Neuro lament disorganization can contribute to neuronal dysfunction and death (34,35). Reduced expression of Ne or Nefm proteins has been shown to cause defect in synaptic function with ensuing behavioral impairment (36,37). Previous reports showed that TDP-43 can bind and stabilize neuro lament mRNAs (2,38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NF-L binds to the cytoplasmic tail of the GluN1/NR1 subunit of the NMDA receptor and to protein phosphatase 1 (PP1) (Ehlers, Fung, O'Brien, & Huganir, 1998;Ratnam & Teichberg, 2005;Terry-Lorenzo et al, 2000). Indeed, NF-L knockout neurons exhibit reduced spine density and length with schizophrenialike behavioral defects (Yuan et al, 2018). INA/NF-I interacts with the PP1 scaffold spinophilin in an age-dependent manner, that is, more INA/NF-I co-IPs with spinophilin in adult compared to postnatal brain (Baucum et al, 2010;Baucum, Strack, & Colbran, 2012).…”
Section: Nfs: Still Many Surprises and Open Questions!mentioning
confidence: 99%